Rapid Induction of Ageing Character in Brandy Products – Part II. Influence of Type of Oak - van Jaarsveld, F.P. van Jaarsveld; Hattingh, S. Hattingh; Minnaar, P. Minnaar (South African Journal of Enology and Viticulture, 2016)
As part of a broader study that investigated techniques for the rapid induction of the needed ageing character in brandy products, the effect of oak type on quality and chemical composition of oak wood extracts and matured and unmatured potstill brandy, is reported on. Extracts, prepared from American and French oak chips supplied by a South African cooper, and from commercially obtained oak, and representing different levels of toasting, were added to 70% (v/v) unmatured pot-still brandy and stored for eight months in glass containers (Schott bottles) at room temperature, or in the case of controls, below 0°C. Matured and unmatured (control) pot-still brandy samples were analysed for wood-derived congeners by means of HPLC and GC. Although French oak initially yielded better quality products, these effects lost prominence and, after eight months maturation, yielded similar sensory quality to American oak. French oak samples had higher concentrations of wood-derived congeners (including eugenol, the furan derivatives and aromatic aldehydes). However, the American oak generally contained higher concentrations of oak lactones than their French counterparts, with higher proportions of the more sensorially potent cis-form of lactone than its trans-isomer.